Specific association of simian virus 40 tumor antigen with simian virus 40 chromatin. - Reiser, J (1980)
Simian virus 40 tumor antigen (SV40 T antigen) was bound to both replicating and fully replicated SV40 chromatin extracted with a low-salt buffer from the nuclei of infected cells, and at least a part of the association was tight specific. T antigen cosedimented on sucrose gradients with SV40 chromatin, and T antigen-chromatin complexes could be precipitated from the nuclear extract specifically with anti-T serum. From 10 to 20% of viral DNA labeled to steady state with [3H]thymidine for 12 h late in infection or 40 to 50% of replicating viral DNA pulse-labeled for 5 min was associated with T antigen in such immunoprecipitates. After reaction with antibody, most of the T antigen-chromatin complex was stable to washing with 0.5 M NaCl, but only about 20% of the DNA label remained in the precipitate after washing with 0.5 M NaCl-0.4% Sarkosyl. This tightly bound class of T antigen was associated preferentially with a subfraction of pulse-labeled replicating DNA which comigrated with an SV40 form I marker. A tight binding site for T antigen was identified tentatively by removing the histones with dextran sulfate and heparin from immunoprecipitated chromatin labeled with [32P]phosphate to steady state and then digesting the DNA with restriction endonucleases HinfI and HpaII. The site was within the fragment spanning the origin of replication, 0.641 to 0.725 on the SV40 map.